Healthcare telemonitoring and business dynamics: challenges and opportunities for SUS - Antonio da Cruz Paula; José Manuel Santos de Varge Maldonado; Carlos Augusto Grabois Gadelha (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To point out challenges and opportunities for the Brazilian Unified Health System (SUS) with the use of telemonitoring to face the increasing costs of non-communicable chronic diseases, based on its general panorama in Brazil, business dynamics and reapplication of data from American studies. METHODS Quali-quantitative approach with exploratory research. The field work focused on the analysis of the national market from private companies, since no experiences or studies related to this theme were identified in the SUS. To analyze the panorama and market dynamics, we investigated the offer of this technology based on the products and services available and their demand by reference hospitals the ten largest private health plan companies. To support the central discussion, we analyzed the reduction of costs with hospital admissions by the SUS due to chronic non-communicable diseases sensitive to telemonitoring (HCDST), using data from Datasus and some American studies from the MEDLINE/PubMed database. RESULTS Although in the embryonic phase, business agents search for new business opportunities, whereas public initiatives for the use of telemonitoring in collective health seem inexistent. The reapplication of U.S. data would reduce spending on HCDST and provide benefits, such as the reduction in emergency room care, acute hospitalizations, readmissions and home care time, among others, which point to even greater economic gains. CONCLUSIONS The development of a major project to reduce HCDST using this technology has the potential to advance in a comprehensive network of primary care, contribute to a greater dynamism of the national productive and innovative base and induce innovations along the chain of this emerging industry.